2005
DOI: 10.1002/xrs.823
|View full text |Cite
|
Sign up to set email alerts
|

PIXE analysis of atmospheric aerosols in Mexico City

Abstract: Samples of atmospheric aerosols were collected at three sites in the metropolitan area of Mexico City and analyzed with particle-induced x-ray emission (PIXE). Stacked filter units of the Davis design were employed to obtain samples of PM 15 (particles with dimensions below 15 µm mean aerodynamic diameter) on polycarbonate filters, divided in two fractions. The study was conducted during the first half of 2002, exposing the filters every 2 days for 24 h, starting at 08 : 00 h. Analysis of variance of the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
4
9
1
1
Order By: Relevance
“…Power plants can have high SO 2 and low CO emissions, however (CAM, 2004), and our findings suggest that anthropogenic SO 2 emissions may have an important impact on MCMA air quality that has been previously overlooked. This has been supported by the recent study of Miranda et al (2005) which found evidence of anthropogenic sources for particulate S in the MCMA.…”
Section: Industrysupporting
confidence: 61%
“…Power plants can have high SO 2 and low CO emissions, however (CAM, 2004), and our findings suggest that anthropogenic SO 2 emissions may have an important impact on MCMA air quality that has been previously overlooked. This has been supported by the recent study of Miranda et al (2005) which found evidence of anthropogenic sources for particulate S in the MCMA.…”
Section: Industrysupporting
confidence: 61%
“…V and Ni are associated to the refinery located to the NE side of the sampling site (Chow et al 2002b), whereas Pb and Ni are emitted by mobile sources (Mugica et al 2002;Mugica et al 2008) near the sampling site. Fe and Ti show similar trends, and their concentrations did not show strong variation with wind direction, suggesting that these metals are associated to geological sources as Miranda et al (2005) indicated. Mn is associated to winds coming from W and NE where a ferromanganese industry and a refinery are located, respectively.…”
Section: Resultssupporting
confidence: 63%
“…Since a mineral transport facility is located near the sampling zone, these metals are likely associated to this source. The relationship between V and Ni indicates the presence of oil combustion and emissions from catalytic processes in the refinery (Chow et al 2004;Miranda et al 2005;Thomas and Morawska 2002). Cu and Zn originate from galvanizing activities and incinerators (Karar et al 2006;Thomas and Morawska 2002) and tire and brake wear (Amato et al 2011).…”
Section: Correlation Between Metalsmentioning
confidence: 98%
See 1 more Smart Citation
“…Tales son los casos de zonas metropolitanas como el Valle de México, Guadalajara y Monterrey. [11][12][13][14] Sin embargo, en la mayoría de las zonas provinciales de la República Mexicana, existe poca información al respecto, tal es el caso de la Ciudad de San Francisco de Campeche, capital del Estado de Campeche, la cual presenta un clima tropical húmedo 15 convirtiéndola en una locación idónea para la realización de estudios de evaluación temprana de calidad del aire. Así mismo, la ciudad es considera Patrimonio Cultural de la Humanidad por la UNESCO desde 1999, por lo que se pretende realizar un estudio sobre contaminantes atmosféricos y su relación con variables meteorológicas en la ciudad y evaluar los efectos de los aerosoles atmosféricos sobre la población y materiales de interés histórico-artístico.…”
Section: Introductionunclassified